Electricity‐Assisted Cancer Therapy: From Traditional Clinic Applications to Emerging Methods Integrated with Nanotechnologies. Issue 3 (23rd December 2022) - Zhong, Songjing; Yao, Shuncheng; Zhao, Qinyu; Wang, Zhuo; Liu, Zhirong; Li, Linlin; Wang, Zhong Lin
Abstract : Inspired by endogenous physiological electric fields in humans, electricity has been widely used as an accessible source of physical stimulation to help treat diseases, including cancer therapy. Electricity can not only be used as a weapon to directly kill cancer cells but also be used as a "switch" to control the anticancer drug delivery systems (DDSs), enabling on‐demand drug release at the lesion sites. Recently, the antitumor electrotherapy based on the induction of tumor cell apoptosis by highly toxic reactive oxygen species (ROS) has been developed. Many studies have proved that the electrical stimulation can mobilize the body's immune system to kill tumors through different mechanisms. When the single electrical therapy is not effective for the treatment of advanced tumors, the integration with immunotherapy is considered as "life‐saving straw." Moreover, with the growing need for convenient, personalized, and telehealth care and treatment, the emerging nanotechnologies such as self‐powered triboelectric nanogenerators (TENGs) are integrated with electrotherapy. This review comprehensively summarizes these developments from clinic applications to new emerging strategies and proposes future challenges and opportunities in this field. Abstract : Herein, different kinds of electricity‐assisted cancer therapeutic methods are reviewed, from the traditional clinically used approaches to the emerging cancer electrotherapy combined with nanotechnologies and nanomedicines, which aims to provide an enlightenment for the future cancer treatment.